2008
DOI: 10.1007/s00213-008-1311-8
|View full text |Cite
|
Sign up to set email alerts
|

Lithium and cognitive enhancement: leave it or take it?

Abstract: It is suggested on the basis of the evidence that the cognitive effects of lithium are best expressed and should, therefore, be sought under conditions of functional or biological challenge to the nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 141 publications
1
16
0
Order By: Relevance
“…Pursuing treatment with lithium seems to be associated with a decrease in the risk of developing dementia 19 . Current neuroanatomical and neurobiological data show favourable neuroprotective properties of lithium, in particular on hippocampus cells 20 . A recent meta‐analysis showed that lithium treatment appears to have limited and minor negative effects on cognition 21 …”
Section: Discussionmentioning
confidence: 99%
“…Pursuing treatment with lithium seems to be associated with a decrease in the risk of developing dementia 19 . Current neuroanatomical and neurobiological data show favourable neuroprotective properties of lithium, in particular on hippocampus cells 20 . A recent meta‐analysis showed that lithium treatment appears to have limited and minor negative effects on cognition 21 …”
Section: Discussionmentioning
confidence: 99%
“…Lithium is rarely prescribed for the first time after the age of 70 because of its narrow therapeutic index and greater risk of neurotoxicity and other side effects with age [48, 95]. However, neuroprotective effects of mood stabilizers, as opposed to chronic stress in neurons, are also described [96]. As they can also have a role in reducing the number of recurrences, these are indirect ways of preventing dementia [49].…”
Section: Treatmentmentioning
confidence: 99%
“…LiCl (200 mg ⁄ kg, i.p., Sigma, St Louis, MO, USA) was dissolved in phosphate buffered saline (PBS) and given 1 h before any intervention once daily from the onset of the learning and memory test to day 7. 17 Control animals received 0.9% saline at the same injection volume (i.p. ).…”
Section: Licl Treatmentmentioning
confidence: 99%